Regional Diversity of Maritime Antarctic Soil Fungi and Predicted Responses of Guilds and Growth Forms to Climate Change - Newsham, Kevin K.; Davey, Marie L.; Hopkins, David W.; Dennis, Paul G. (Frontiers in Microbiology, 2021)
We report a metabarcoding study documenting the fungal taxa in 29 barren fellfield soils sampled from along a 1,650 km transect encompassing almost the entire maritime Antarctic (60–72 °S) and the environmental factors structuring the richness, relative abundance and taxonomic composition of three guilds and growth forms. The richness of the lichenised fungal guild, which accounted for 19% of the total fungal community, was positively associated with mean annual surface air temperature (MASAT), with an increase of 1.7 OTUs of lichenised fungi per degree Celsius rise in air temperature. Soil Mn concentration, MASAT, C:N ratio and pH value determined the taxonomic composition of the lichenised guild, and the relative abundance of the guild was best predicted by soil Mn concentration. There was a 3% decrease in the relative abundance of the saprotrophic fungal guild in the total community for each degree Celsius rise in air temperature, and the OTU richness of the guild, which accounted for 39% of the community, was negatively associated with Mn concentration. The taxonomic composition of the saprotrophic guild varied with MASAT, pH value and Mn, NH4+-N and SO42- concentrations. The richness of the yeast community, which comprised 3% of the total fungal community, was positively associated with soil K concentration, with its composition being determined by C:N ratio. In contrast with a similar study in the Arctic, the relative abundance and richness of lichenised fungi declined between 60 °S and 69 °S, with those of saprotrophic Agaricales also declining sharply in soils beyond 63 °S. Basidiomycota, which accounted for 4% of reads, were much less frequent than in vegetated soils at lower latitudes, with the Ascomycota (70% of reads) being the dominant phylum. We conclude that the richness, relative abundance and taxonomic composition of guilds and growth forms of maritime Antarctic soil fungal communities are influenced by air temperature and edaphic factors, with implications for the soils of the region as its climate changes during the 21st century.